Analisis Pengaruh Tingkat Pengangguran Terbuka Dan Inflasi Terhadap Pertumbuhan Ekonomi Diprovinsi Lampung (2012-2021) - Sri Handayani; Vita Mutia Cahyani; Winda Ariyani; Muhammad Kurniawan (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to analyze the influence of the open unemployment rate and inflation on economic growth in Lampung Province in the 2012-2021 period. The data used is secondary data obtained from the Lampung Provincial Government Financial Statistics and the Central Statistics Agency. The analytical methods used include normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The results of the analysis show that the open unemployment rate and inflation have a negative influence on economic growth in Lampung Province. The implication of this research is the need to increase investment, improve workforce qualifications, stable inflation policies, and economic diversification to increase economic growth in Lampung Province.